Facile synthesis and surface modification of bioinspired nanoparticles from quercetin for drug delivery. (24th August 2018) - Sunoqrot, Suhair; Al-Shalabi, Eveen; Messersmith, Phillip B.
Abstract : Bioinspired surface-modifiable nanoparticles are synthesized from quercetin by oxidative self-polymerization as a promising nanoscale platform for drug delivery. Abstract : Nanoparticle-mediated drug delivery has demonstrated great potential to treat various diseases especially cancer. However, there is an unmet need for the scalable synthesis of multifunctional nanoparticles to meet the complex challenges of drug delivery. Here we show that we can synthesize nanoparticles from the polyphenol quercetin, which can be conveniently functionalized with ligands and drug molecules by simple mixing under ambient conditions. Nanoparticles (∼30–40 nm in diameter) were formed by oxidative self-polymerization of quercetin in alkaline buffer (pH 9). The reactivity of oxidized polyphenols was exploited to immobilize amine-terminated methoxy poly(ethylene glycol) on the nanoparticles' surface for steric stability, followed by loading with doxorubicin as a model drug. Surface modification of the nanoparticles was confirmed by X-ray Photoelectron Spectroscopy. An antioxidant assay showed that the nanoparticles retained some antioxidant activity. The nanoparticles were readily internalized by KB cells via an endo-lysosomal pathway. Doxorubicin-loaded nanoparticles showed a drug loading of 35.6 ± 4.9% w/w with a loading efficiency of 88.9 ± 12.4%, sustained drug release, and potent cytotoxicity in vitro . Our findings demonstrate a promising new application for naturally occurring polyphenols as a renewable source of drug delivery nanocarriers that can be synthesized at low cost with minimal equipment.